Remote sensing in resource geography - Saini, R. R.; Kalwar, S. C., 1947- (Jaipur, India : Pointer Publishers : Distributed by Aavishkar Publishers' Distributors, 1991)
Study based on Jaipur District, Rajasthan.
Includes index.
Includes bibliographical references (p. [180]-186).
Keywords: Remote sensing -- India -- Jaipur (District)